The Effects of Biological, Synthetic and Traditional Dressing on Pain Intensity of Burn Wound in children - Sh Rasuli; M Lotfi; B Seyedamini; V Zamanzadeh; B Naghili (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Although burn wound and its pain management has gradually improved in recent years, but selection of an efficient dressing is yet a global problem and a major challenge for health care personnel. The aim of this study was comparing the effect of biological, synthetic and traditional dressing on burn wound pain in children.   Material and Methods: This experimental study was conducted on 90 patients who were treated in burn ward of Sina health center in Tabriz city during 2008-2009. Patients were randomly assigned into three groups: synthetic dressing group with dressing changes every 3 days (30 patients), biological dressing group (30 patients) and traditional dressing group (30 patients), with daily dressing changes. Pain intensity ( procedural pain and backgrounds pain), was evaluated using NIPS, CHEOPS and Wong Baker at days 3 and 6 . Data was analyzed by descriptive (Mean, frequencies) and inferential statistics ( Kruskal-wallis, Chi-square ) using SPSS-PC (v. 13).   Results: Pain score during dressing change were compared among synthetic, biological and traditional dressing groups. Mean ranks of pain in synthetic dressing group was significantly lower than other groups, in third morning and night of hospitalization (procedural and background pain) (24.7 versus 56.1 and 53.5 28.7 versus 54.5 and 51.3, respectively, P < 0.001) and in the morning of sixth day of hospitalization (procedural pain) (25.3 versus 45.2 and 51.6, respectively, P < 0.001).   Conclusions: This study showed that synthetic dressing decreased pain and increased patient comfort because of reducing the frequency of dressing changes. The results confirm the efficacy of synthetic dressing for the treatment of partial and deep thickness burns. It provides insights and suggestions for future research on modern dressing for burn wounds treatment.   Received: 28 Sep 2013   Accepted: 14 Dec 2013